Crop insurance for climate resilience: Priorities for South Africa’s G20 Presidency - Kramer, Berber; Hill, Ruth Vargas (South African Institute of International Affairs, 2025)
This policy brief argues that South Africa’s G20 Presidency offers a pivotal opportunity to elevate crop insurance as a core instrument for strengthening climate resilience across Africa. As droughts, floods and weather variability intensify, climate risks increasingly threaten smallholder farmers who rely on rain-fed production, undermining livelihoods and regional food security. The brief highlights crop insurance as a practical risk-transfer mechanism that can safeguard incomes, stabilise food supply, and protect vulnerable households from climate-related shocks. It outlines how crop insurance aligns closely with key G20 working groups—Environment & Climate Sustainability, Disaster Risk Reduction, and Agriculture—each emphasizing adaptation, inclusive risk-sharing and resilient food systems. To realise this potential, the brief calls for investment-enabling policies, innovative financing suited to smallholders, and stronger integration of insurance within climate-risk management strategies, positioning crop insurance as a scalable and actionable priority for South Africa’s G20 agenda.